Effects of Compaction Water Content on Water Retention and Deformation Behavior of Compacted Loess - S. J. Di; Y. Zhang; H. Zhou; W. L. Xie; X. L. He; Y. T. Li; Q. Y. Mu (Advances in Civil Engineering)
Compacted loess is widely used as a construction material in engineering practices. The compaction dry density and compaction water content have significant effects on the hydromechanical behavior of compacted loess, thereby influencing the serviceability and safety of engineering structures. The former was widely studied in previous studies, while the latter is rarely known. In this study, the water retention, compression, and collapse behavior of compacted loess at different compaction water contents are investigated through pressure plate and oedometer tests. Microstructure analysis was carried out for insight analysis of the test results. The air entry value and yield stress of compacted loess decreased by 64% and 50%, respectively, with the compaction water content increasing from 12.4% to 19.0%. This is due to the fact that the number of clods increases with increasing the compaction water content, leading to many large-sized pores (i.e., diameter > 1,000 μm) and weaker soil skeletons. The influence of compaction water content on the water retention and compression behavior of loess is more pronounced at lower compaction dry densities and lower testing water contents, respectively. In addition, the specimen shows smaller collapse indexes at higher compaction water contents, mainly because of the larger deformation induced by the initial compression.